Hubungan Tingkat Pengetahuan Dan Sikap Ibu Terhadap Kejadian Stunting Di Puskesmas Pamulang - setyaningsih, putri; Fitriani, Dewi; Arimurti, Ikada Septi Arimurti; Rahmi, Junaida; Lestari, R Tri Rahayuning; Puji, Lela Kania Rahsa; Hasanah, Nur; Aliyah, Hopipah Hilmatul; Aisah, Siti (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2024)
ABSTRACTBackground: Stunting is a condition of malnutrition that is related to past nutritional deficiencies, so it is a chronic nutritional problem. Globally, Stunting data in 2020 is that there are 149.2 million children under 5 years experiencing Stunting or around 22%, in Indonesia in 2021 the prevalence of Stunting is 24.4%, and in 2022 the prevalence of Stunting is 21.6%, data Stunting in Banten Province in 2021 is 24.5% and in 2022 is 20%, South Tangerang the prevalence of stunting is (9.0%). Even though in Indonesia the number of stunting incidents has decreased, stunting is still a serious problem and the focus is on efforts to reduce the number of stunting incidents in Indonesia. Research Objectives: to find out the mother's knowledge and attitude towards stunting in toddlers at the Pamulang Health Center. Research Method: quantitative descriptive research method, with a cross-sectional approach with the number of research respondents being 60 mothers of toddlers at the Pamulang Community Health Center, using univariate and bivariate analysis with the Chi-square test. Research Results: More than half of the gender is male, namely 33 respondents (55.0%), more than half of the children aged 12-35 months, namely 36 respondents (60.0%), almost half of the mother's level of knowledge about Stunting is knowledgeable good, namely 23 respondents (38.3%), almost half of the mothers had poor attitudes, namely 24 respondents (40.0%), more than half of the incidents occurred in toddlers, namely 35 respondents (58.3%) toddlers did not experience stunting. Conclusion: There is a relationship between the level of knowledge regarding the incidence of stunting in toddlers with a p-value of 0.007, and there is a relationship between the mother's attitude towards the incidence of stunting with a p-value of 0.004. Suggestion: Parents are expected to monitor their toddlers every month at health services to determine their growth and development. ABSTRAKA B S T R A KLatar Belakang: Stunting adalah salah satu keadaan malnutrisi yang berhubungan dengan ketidak cukupan zat gizi masa lalu sehingga termasuk dalam masalah gizi yang bersifat kronis. Secara global data Stunting pada tahun 2020 yaitu terdapat 149,2 juta anak di bawah 5 tahun mengalami Stunting atau sekitar 22%, di Indonesia pada tahun 2021 prevalensi Stunting 24,4%, dan di tahun 2022 prevalensi Stunting yaitu 21,6%, data Stunting di Provinsi Banten pada tahun 2021 yaitu 24,5% dan tahun 2022 yaitu 20%, Tangerang selatan prevalensi Stunting (9,0%). Walaupun di Indonesia angka kejadian sunting mengalami penurunan namun Stunting masih menjadi masalah serius dan fokus dalam upaya penurunan angka kejadian Stunting di Indonesia. Tujuan Penelitian: untuk mengetahui pengetahuan dan sikap Ibu terhadap kejadian Stunting pada balita di Puskesmas Pamulang. Metode Penelitian: metode penelitian deskriptif kuantitatif, dengan pendekatan crossectional dengan jumlah responden penelitian 60 orang ibu yang memiliki balita di puskesmas pamulang, menggunakan analisis univariat dan bivariat dengan uji Chi-squere. Hasil Penelitian: Jenis kelamin lebih dari setengahnya berjenis kelamin laki-laki yaitu 33 responden (55,0%), lebih dari setengahnya usia balita 12-35 bulan yaitu 36 responden (60,0%), hampir setengahnya tingkat pengetahuan ibu tentang Stunting berpengetahuan baik yaitu 23 responden (38,3%), hampir setengahnya ibu memiliki sikap yang kurang yaitu 24 responden (40,0%), lebih dari setengahnya kejadian pada balita yaitu 35 responden (58,3%) balita tidak mengalami Stunting. Kesimpulan: Adanya hubungan antara tingkat pengetahuan terhadap kejadian Stunting pada balita dengan p-value 0,007, dan terdapat hubungan antara sikap Ibu terhadap kejadian Stunting dengan p-value 0,004. Saran: Bagi orang tua di harapkan dapat memantau balitanya setiap bulan ke pelayanan kesehatan untuk mengetahui pertumbuhan dan perkembangan balitanya.